OBSERVACIONES TEXTUALES A OV. MET. 3.640-642 - Ángela Suárez del Río (Exemplaria Classica, 2016)
This article presents textual observations on Ov. met. 3.640-2 in an attempt to establish the genuine text. The manuscript and editorial traditions are reviewed and analysed, as well as the main critical contributions hitherto made to these verses.